The relationship between minimum alcohol prices, outlet densities and alcohol-attributable deaths in British Columbia, 2002-09 - Zhao, J.; Stockwell, Tim; Martin, G.; Macdonald, S.; Vallance, K.; Treno, A.; Ponicki, W.; Tu, A.; Buxton, J. (2013)
Aim: To investigate relationships between periodic increases in minimum alcohol prices, changing densities of liquor stores and alcohol-attributable (AA) deaths in British Columbia, Canada. Design: Cross-section (16 geographic areas) versus time-series (32 annual quarters) panel analyses were conducted with AA deaths as dependent variables and price, outlet densities and socio-demographic characteristics as independent variables. Setting and participants: Populations of 16 Health Service Delivery Areas in British Columbia, Canada. Measurements: Age-sex-standardized rates of acute, chronic and wholly AA mortality; population densities of restaurants, bars, government and private liquor stores; minimum prices of alcohol in dollars per standard drink. Findings: A 10% increase in average minimum price for all alcoholic beverages was associated with a 31.72% [95% confidence interval (CI):±25.73%, P<0.05] reduction in wholly AA deaths. Significantly negative lagged associations were also detected up to 12 months after minimum price increases for wholly but not for acute or chronic AA deaths. Significant reductions in chronic and total AA deaths were detected between 2 and 3 years after minimum price increases. Significant but inconsistent lagged associations were detected for acute AA deaths. A 10% increase in private liquor stores was associated with a 2.45% (95% CI:±2.39%, P<0.05), 2.36% (95% CI:±1.57%, P<0.05) and 1.99% (95% CI:±1.76%, P<0.05) increase in acute, chronic and total AA mortality rates. Conclusion: Increases in the minimum price of alcohol in British Columbia, Canada, between 2002 and 2009 were associated with immediate and delayed decreases in alcohol-attributable mortality. By contrast, increases in the density of private liquor stores were associated with increases in alcohol-attributable mortality.